Laboratory Management in Improving the Tri Dharma of Higher Education in The Department of Mining Engineering - Winarno, Eddy; Cahyadi, Tedy Agung; Wiyono, Bagus; Lusantono, Oktarian Wisnu; Ardian, Aldin; Syukron, M.; Haqa, Shofa Rijalul; Suharyadi, Heru; Vergiagara, Vega; Y, M. Rahman; Firmansyah , Ilham (RSF Conference Series: Business, Management and Social Sciences, 2021)
Improving the quality of laboratory services must always be improved in improving the quality of the tri dharma of higher education. Good laboratory management is one of the supporting factors, for that reason, the Department of Mining Engineering manages the laboratory. Laboratory management, in this case, is the laboratory equipment inventory system and laboratory control system. This system will be used to carry out monitoring data on the use of website-based laboratory equipment where the use of laboratory equipment must be carried out systematically. The first step is to create a web system for administration and inventory in the laboratory. In this study, in conducting website-based lab management, it is also necessary to map the problems faced by students in relation to services and supporting infrastructure in the laboratory.